Cladistic reanalysis and historical biogeography of the genus Lycinus Thorell, 1894 (Araneae: Mygalomorphae: Nemesiidae) with description of two new species from western Argentina - Ferretti, Nelson Edgardo (2015)
Background: The genus Lycinus includes ten species, one from Argentina, eight from Chile, and one from Brazil. Two new species from western Argentina are described, and some data on natural history are presented. A cladistic reanalysis with the newly described species is carried out, and a reconstruction of ancestral areas and primary Brooks Parsimony Analysis are performed. The origins of the main groups of Lycinus are also diResults: Lycinus lagigliai sp. nov. and Lycinus nevadoensis sp. nov. are described. The distribution of these species comprised western Argentina at Mendoza province. The cladistic reanalysis showed Lycinus as monophyletic supported only by the synapomorphy of dorsal spines on male palpal tibia. The tree topology was as follows: (Lycinus epipiptus, Lycinus domeyko ((Lycinus longipes, L. nevadoensis sp. nov.) (Lycinus portoseguro, L. lagigliai sp. nov.)) (Lycinus caldera (Lycinus gajardoi, Lycinus choros)) (Lycinus tofo, Lycinus quilicura)). The biogeographical analysis showed a close relationship of the species from the Andean region and the South American Transition Zone. The reconstruction of ancestral areas recognized four vicariant nodes. Conclusions: A hitherto two unknown Lycinus species are recognized and formally described, along with a cladistic reanalysis and historical biogeographical hypotheses.